Mixed-methods study to assess delay among patients with tuberculosis in an urban setting of Bangladesh - Shahriar Ahmed; Samanta Biswas; Tanjina Rahman; Ahammad Shafiq Sikder Adel; S. M. Zafor Shafique; Refah Tamanna; Kamal Ibne Amin Chowdhury; Sayera Banu (PLoS ONE, 2025)
Background Tuberculosis (TB) regained its position as the leading cause of death globally from a single infectious disease agent in 2024. Delayed diagnosis and treatment hamper effective TB control. We investigated the duration of diagnostic and treatment delay along with the associated factors among people with pulmonary TB in Bangladesh. Methods A mixed-method study was conducted between December’19 and March’21, at icddr,b TB Screening and Treatment Centres (TBSTCs), Dhaka. We interviewed people with TB (PWTB) seeking care at these TBSTCs using a structured questionnaire to collect data on socio-demographic, clinical and healthcare seeking behaviors. We used established frameworks to define stages of delay and associated factors. Qualitative interviews were conducted among a subset of participants to gain further insight into the factors associated with delay. Results We enrolled 895 PWTB with mean (±SD) age 36.6 (±16.1) years; majority of participants were males (69.9%) and living in urban areas (82.3%). The median (IQR) patient delay estimated was 47 (29–72) days, with diagnostic delay 45 (30–70) days and treatment delay 2 (2–4) days. The predictors of delay were those with diabetes (OR 2.0, 95% CI – 1.11, 3.42), who initially self-treated (OR 2.1, 95% CI – 1.09, 3.88), and were bacteriologically diagnosed (OR 3.7, 95% CI – 1.31, 10.46). Qualitative approach supported the quantitative findings and revealed the practice of visiting formal physicians during worsening illness, neglecting to acknowledge signs or symptoms consistent with TB, lack of TB related knowledge, and financial insolvency as major reasons for delay. Conclusion Our findings showed that improper health-seeking behavior is one of the major drivers of patient delay. Thus, targeted programmatic intervention to raise community awareness on TB and its care services with a special focus on informal providers can help reduce this delay.